Osteopontin regulates right ventricular failure through integrin ανβ3/PERK/CHOP-dependent inflammatory and apoptotic pathways - Yang, Xiaomei; Wang, Xuyang; Li, Kai; Deng, Qiming; Hou, Yonghao; Xi, Guangmin; Lu, Kangping; Liu, Zihua; Bai, Yu; Wu, Jianbo; Yu, Jingui; Zhang, Peng (Frontiers in Immunology, 2025)
IntroductionRight ventricular failure is a life-threatening condition commonly associated with obvious immune responses in its progression. This study aims to investigate the role of osteopontin (OPN) in right ventricular failure pathogenesis and evaluate its potential as a therapeutic target.MethodsThis study adopted a multi-level design. First, immune-related differentially expressed genes (IRDEGs) were identified using the GEO database (GSE161473) and immune cell composition analysis via ImmuCellAI. A right ventricular failure (RVF) rat model was established, and Western blot, RT-qPCR, and immunohistochemical/immunofluorescence analyses were performed to assess OPN expression and inflammatory infiltration. In vitro, neonatal rat cardiomyocytes were treated with recombinant OPN to examine changes in endoplasmic reticulum stress markers, while the Integrin-ανβ3 inhibitor LM609 was used to delineate OPN’s mechanism of action. Finally, in a clinical study, serum OPN levels were measured by ELISA and compared with NT-proBNP through correlation and Receiver Operating Characteristic (ROC) analyses.ResultsWe found that OPN triggered cardiomyocyte inflammatory responses by activating endoplasmic reticulum stress via the Integrin-ανβ3/PERK/CHOP pathway. OPN exhibited concentration-dependent effects on cardiomyocyte survival: at 2 μg/ml it showed protective effects through BCL-2 modulation, while higher concentrations promoted apoptosis. Importantly, serum OPN levels strongly correlated with NT-proBNP and disease severity in RVF patients.DiscussionThese findings identify OPN as a crucial mediator of RVF pathogenesis through the regulation of inflammatory and apoptotic pathways, establishing its potential as a promising therapeutic target.